PENGARUH PROFITABILITAS, OPINI AUDIT, UKURAN PERUSAHAAN, TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - Rakhmi Ridhawati; - Fitriadi (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract, This research was conducted to test empirically Effect of Profitability, Opinion Audit and Company Size of the Timeliness of Financial Reporting to the Property Company Listed in Indonesia Stock Exchange (BEI). Samples in this research were 30 property company that has a complete set of financial statements from 2008 to 2009. The results showed that the profitability as measured by ROA affect the timeliness of financial reporting company property. While the audit opinion and the size of the company does not affect the timeliness of financial reporting property company listed on the Indonesia Stock Exchange.